A Novel Idea to Prevent Accidental Prick by Kirschner Wire during Orthopedic Surgeries - Vetrivel C Sengodan; Vijay Krishnan A Subramaniyan; Jenson Moses; Sreehari Vikram; Venkatesh Venkatachalam (Journal of Orthopedics and Joint Surgery)
Introduction: Kirschner wires were first utilized in orthopedic surgery by Martin Kirschner in 1909. These days, Kirschner wires are among the most often used implants found in operating rooms. A tool for limited internal fixing is Kirschner wires. It serves as an implant for various surgical procedures as well as for initial fixation. Kirschner wires come in a range of diameters and lengths. Kirschner wires were originally made of stainless steel, but they are now also made of titanium. Kirschner wires are sharp at both ends. If it is used for stabilization of fracture, one of the sharp ends is exposed and the operating team is at risk of getting pricked by the sharp end of Kirschner wire. The aim of the study is to discuss the novel idea of avoiding accidental pricks from the sharp end of the Kirschner wire during orthopedic surgeries. Materials and methods: Fifty patients were included in the study of which, 35 were males and 15 were females. Patients of the age-group 20–60 years were included in the study. The study period was from January to July 2023. The study was conducted in the Institute of Orthopedics and Traumatology, Government Coimbatore Medical College Hospital after ethical clearance. Results: In all 50 patients, covering the Kirschner wires with the respective infant feeding tube successfully prevented accidental pricks to the operating team during orthopedic surgeries, namely distal radius fractures, supracondylar humerus fractures of adults, distal femur fractures, and in small long bone fractures like metatarsals and phalangeal bones. In all 50 cases, covering the Kirschner wire with the respective infant feeding tube successfully prevented accidental prick injury during orthopedic surgeries. Discussion: Kirschner wire is a sharp stainless steel wire and was introduced in 1909 by Martin Kirschner. This wire is now routinely used in orthopedic surgeries as a limited internal fixation device. Kirschner wire is a useful tool for percutaneously fixing a variety of fractures, including supracondylar humerus and distal radius fractures. In cases of fractures of small, lengthy bones, such as those involving hand and foot orthopedic procedures, Kirschner wires are utilized as a limited internal fixation method. Kirschner wires are also a useful tool for deformity treatment when used with the Ilizarov external fixator.